Association between serum vitamin D status and uterine leiomyomas: a case-control study - Chukwuemeka Chukwubuikem Okoro; Okechukwu Christian Ikpeze; George Uchenna Eleje; Gerald Okanandu Udigwe; Chukwuemeka Okwudili Ezeama; Joseph Odirichukwu Ugboaja; Chukwunonso Isaiah Enechukwu; Osita Samuel Umeononihu; Chukwudi Anthony Ogabido; Charlotte Blanche Oguejiofor; Tobechi Kingsley Njoku; Richard Obinwanne Egeonu; et al. (Korean Society of Obstetrics and Gynecology, 2024)
Objective Uterine leiomyoma is a common gynecological condition that negatively affects women's quality of life. Vitamin D plays an important role in tumor development and progression. However, clinical studies comparing serum vitamin D levels between women with and without uterine leiomyomas are limited and inconclusive. This study aimed to compare serum vitamin D levels in women with and without uterine leiomyomas. Methods This hospital-based case-control study included 150 women who visited a gynecological clinic. The cases included 75 women with uterine leiomyoma, whereas the controls included 75 age-and parity-matched participants without uterine leiomyoma. Serum vitamin D levels were measured in each participant and volumes of the uterine leiomyomas were determined using the water displacement method following myomectomy. The statistical significance was inferred at P<0.05. Results The mean serum vitamin D level was 15.26±4.96 ng/mL and 22.45±6.93 ng/mL for the case and control groups, respectively. The difference was statistically significant (t-value −7.302 and P<0.001). Within the fibroid group, nine (12.0%), 49 (65.33%), and 17 (22.67%) participants had vitamin D deficiency, insufficiency, and sufficiency, respectively; and in the control group, two (2.67%), 24 (45.33%), and 39 (52.0%) participants had vitamin D deficiency, insufficiency, and sufficiency, respectively. There was significant negative correlation between the fibroid volume and the serum vitamin D level (r=−0.591, P<0.001). Conclusion Women with uterine leiomyoma had lower vitamin D levels than women in the control group. Lower vitamin D levels were associated with larger fibroid masses. Therefore, vitamin D supplementation may reduce fibroid growth and development.